Glycopeptides of murine leukemia viruses. II. Comparison of xenotropic and dual-tropic viruses. - Kemp, M C (1980)
The glycosylation patterns of the gp70 glycoproteins of xenotropic and dualtropic murine leukemia virus (MuLV) were compared with those of ecotropic viruses. Ecotropic viruses contain a large glycopeptide size class designated G1 (molecular weight, approximately 5100), and such glycopeptides were not detected in xenotropic viruses grown in mink cells nor in dual-tropic viruses grown in mouse or mink lung cells. Both xenotropic and dual-tropic MuLV had glycopeptide size classes designated G2, G3, and G4 (molecular weights, approximately 2900, 2,200, and 1,500, respectively). G2 glycopeptides of xenotropic and dual-tropic MuLV were shown to be resistant to endo-beta-N-acetylglucosaminidase H, whereas G3 and G4 glycopeptides were susceptible. The relative abudance of glycopeptide G3 was increased in xenotropic and dual-tropic viruses as compared with ecotropic viruses, whereas the relative amount of G4 was decreased in xenotropic viruses. The similarity in the glycosylation patterns of a number of xenotropic and dual-tropic viruses suggests that glycosylation sites are highly conserved within the env gene products of each of these classes of viruses.